Analysis of the Use of the Canva Application as a Learning Medium for Community Education Students at the University of Riau - Chyntia Meisyaharta; Dian Alpita Sari; Shyfa Meuthiasyah; Rika Fitri Ramadani (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the use of the Canva application as a learning medium for Community Education students at the University of Riau. The study employed a descriptive qualitative approach with five students selected purposively as the research subjects. Data collection was conducted through semi-structured interviews and analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Canva was utilized to present learning materials in visual forms such as presentations, posters, and infographics. The use of Canva encouraged improvements in creativity, visual communication skills, and student engagement in the learning process. In addition, Canva helped facilitate material comprehension and increased learning motivation. However, there were obstacles in the form of limited features and dependence on internet connectivity. Overall, Canva is effective as a digital learning medium that supports active and creative learning, although it still needs to be balanced with a good understanding of the material.